HADIS PENDIDIKAN : PENELUSURAN AKAR PENDIDIKAN JASMANI DALAM HADIS - Lazuardi, Lazuardi (AIN Padangsidimpuan, 2014)
Physical education is an integral part of the overall education. Generally, this type of education always be integrated with physical education and health. Physical education is not only related with physical development but is closely connected with the spiritual and mental health. A popular saying proves it